The Effect of Liquidity, Leverage and Sales Growth on Financial Distress with Profitability as a Moderating Variable: Empirical Study of Textile and Garment Industry Sub-Sector Companies - Sintia; Rays, Muh (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To identify and analyze the effect of the variables Liquidity, Leverage and Sales Growth on Financial Distress by adding a moderating variable, namely profitability in strengthening the relationship between variables. Background Problems: The Covid-19 pandemic has had an impact on reducing the amount of production for the garment industry utilization rate from 84.93% to 65.00%. Novelty: The addition of a moderating variable namely profitability in strengthening the relationship between the independent variables (Liquidity, Leverage and Sales Growth) to the dependent variable (Financial Distress). Research Methods: Purposive sampling method with a total of 16 companies in the textile and garment industry, using the modified Altman Z-score method with SPSS 25. Finding/Results: Profitability is able to weaken the effect of Liquidity and leverage on financial Distress, while Profitability cannot be a moderation (unable to weaken or strengthen) the effect of Sales Growth on financial distress. Conclusion: The prediction of financial difficulties that have an impact on bankruptcy is not entirely accurate in predicting bankruptcy, but the results of the analysis are still important to be used as an early warning of predictions of financial difficulties and as information for companies to prevent early on as well as evaluation material to improve financial performance